2016
DOI: 10.1038/srep34789
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the CD8 T cell response by human papillomavirus type 16 E7 occurs in Langerhans cell-depleted mice

Abstract: Human papillomavirus (HPV) is an epitheliotropic virus that is the primary causal agent for cervical cancer. Langerhans cells (LC) are skin antigen presenting cells that are reduced in number in HPV-infected skin. The aim of this study was to understand the immune-modulatory effects of HPV16 E7 on LC and on the CD8 T cell response to a skin-expressed antigen. To test this, HPV16 E7 was expressed in mouse skin keratinocytes with the model antigen ovalbumin (Ova). Similar to what is observed in HPV-infected huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…There is now also substantial evidence supporting the immune suppressive effects of E7. Consistent with the suppression by E7 observed here, we also previously have shown that the cytotoxic T cell response to OVA was suppressed in vivo when E7 was co-expressed in the OVA-expressing epidermal keratinocytes 37 . Furthermore, E7 transgenic skin grafted onto immune competent E7-immunised recipient mice is not rejected 39 , an immune suppressive environment is created following mast cell infiltration in the HPV16 E7 skin-expressing transgenic mouse 40 , and surface MHC-I is down-regulated on cells expressing E7 41 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is now also substantial evidence supporting the immune suppressive effects of E7. Consistent with the suppression by E7 observed here, we also previously have shown that the cytotoxic T cell response to OVA was suppressed in vivo when E7 was co-expressed in the OVA-expressing epidermal keratinocytes 37 . Furthermore, E7 transgenic skin grafted onto immune competent E7-immunised recipient mice is not rejected 39 , an immune suppressive environment is created following mast cell infiltration in the HPV16 E7 skin-expressing transgenic mouse 40 , and surface MHC-I is down-regulated on cells expressing E7 41 .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, LCs were activated by LPS in vitro , LCs from epidermal sheets were competent to migrate from the epidermis, and LCs exposed to control microparticles and OVA provoked an OVA-specific cytotoxic response. In addition, we and others have shown that cytotoxic T cell responses can be generated to skin-expressed OVA in vivo 37 , 38 . There is now also substantial evidence supporting the immune suppressive effects of E7.…”
Section: Discussionmentioning
confidence: 83%
“…Retained HPV gene expression is associated with resistance to CRT and death from cervical cancer HPV, the most common cause of cervical cancer, is known to evade the immune system 27 as well as actively suppress it by decreasing activation and cytotoxic activity of CD8 T-cells 28,29 and by inhibiting stimulator of interferon genes (STING) resulting in decreased type I interferon signaling which others have shown causes a blunted radiation mediated antitumor immune response. 30,31 We therefore hypothesized that the decreased immune response observed in patients DOD is associated with increased HPV gene expression during CRT.…”
Section: Tumors From Patients Dod Have Decreased Lymphocyte Infiltratmentioning
confidence: 99%
“…As a consequence of the E‐cadherin downregulation on infected keratinocytes (described above), LCs leave the infected tissue. Recently, it was demonstrated in a mouse model that the E7 protein alone is also sufficient to reduce LCs in the skin …”
Section: Extracellular Hpv Immune Evasion Strategies Affecting Immunementioning
confidence: 99%
“…Recently, it was demonstrated in a mouse model that the E7 protein alone is also sufficient to reduce LCs in the skin. 60…”
Section: Antigen Presenting Cellsmentioning
confidence: 99%